Trends in Birth Weight and the Incidence of Low Birth Weight and Advanced Maternal Age in Korea between 1993 and 2016 - Kim, Hye-Eun; Song, In Gyu; Chung, Sung-Hoon; Choi, Yong-Sung; Bae, Chong-Woo (Journal of Korean medical science, 2019)
As the aging society progresses, the average age of mothers is also increasing. Advanced maternal age has been known to be associated with perinatal outcomes, as well as birth weight (BW). In this study, we aimed to investigate the perinatal factors associated with low birth weight infants (LBWIs) using birth statistics of the Korean population. Birth statistics between 1993 and 2016 from the Korean Statistical Information Service were reviewed. We investigated 12,856,614 data points, which included the number of births, BWs, percentage of preterm births and LBWIs, multiple pregnancies, and maternal age. The proportion of LBWIs delivered by mothers of advanced maternal age has gradually increased since 1993. In addition, the proportion of older mothers (≥ 35 years old) giving birth to LBWIs has increased over the years. Average BW has a negative correlation with the ratio of preterm births, LBW, multiple births, and advanced maternal age. The mean BW also has a negative correlation with maternal age. This study shows that the average BW continues to decline, and the incidence of LBWIs is increasing in Korea since 1993. This study also revealed that several perinatal factors, including percentage of preterm births, LBWIs, multiple births, and maternal age influence the mean BW. Although this study did not investigate the effects of decreasing mean BW on perinatal health, future research is worth discussing.